Stereotactic Administration of Edaravone Ameliorates Collagenase‐Induced Intracerebral Hemorrhage in Rat. (8th July 2016) - Zhang, Yan; Yang, Yang; Zhang, Guang‐Zhu; Gao, Mou; Ge, Guang‐Zhi; Wang, Qin‐Qin; Ji, Xin‐Chao; Sun, Yi‐Lin; Zhang, Hong‐Tian; Xu, Ru‐Xiang
Summary: Background: Edaravone is widely used for treating ischemic stroke, but it is not still confirmed in intracerebral hemorrhage (ICH) as an ideal medication targeting the brain parenchyma. We aimed to investigate the neuroprotective effects of stereotactic administration of edaravone (SI) into the brain parenchyma. Methods: Intracerebral hemorrhage rat models were established by infusion of collagenase into the caudate nucleus. Neural functional recovery was assessed using modified neurological severity scores (mNSS). A comparative study of therapeutic effects between SI and intraperitoneal injection of edaravone (IP) involved in cerebral edema, blood–brain barrier (BBB) permeability, hematoma absorption, inflammatory response and neuronal apoptosis. Results: Compared with IP, the mNSS was significantly ( P < 0.05) improved by SI; cerebral edema and BBB permeability were dramatically ameliorated ( P < 0.05); IL‐4 and IL‐10 levels increased, but IL‐1β and TNF‐α levels significantly decreased; neuron apoptosis decreased markedly ( P < 0.05); and caspase‐3 and Bax expression significantly dropped, but Bcl‐2 increased in SI group ( P < 0.05). Conclusion: SI markedly improved neurological deficits in ICH rat models via antiinflammatory and antiapoptosis mechanisms and promoted M2‐type microglia differentiation. SI was effective in rats with collagenase‐induced ICH.